A Framework for information and communications technology policy reviews : helping countries leverage ICT for development (UN New YorkUS, 2014)
Builds on UNCTAD's longstanding work on ICT policies and on ICT measurement for economic development and trade. Identifies key challenges and solutions in relation to the strategic review of ICT policy plans including leadership, implementation mechanisms, monitoring and review, coordination, institutional framework and the roles of each stakeholder.
Keywords: INFORMATION TECHNOLOGY